An E-Library System Integrated with Bookshelf and Recommendation Components - Folasade Olubusola Isinkaye; Tomiwa John Fred-Yusuff (Journal of Applied Intelligent System, 2022)
Apparently, most students in Nigeria are facing challenges as regards to the lack of portability, stress, time wastage and inadequate resources in terms of accessing the school libraries, as well as the inefficiency of the existing e-library, leading to the reduction in the number of students that do access the libraries. Research has shown that most students no longer believe in the physical libraries and have developed interest in electronic resources. Hence, an e-library system enhanced with book recommendation component could serve as a solution to these problems. Several researchers have repeatedly attempted to develop various solutions to this problem using various methodologies and approaches in order to provide a digital library that could address the aforementioned problems. In this work, an e-library system integrated with recommendation component was designed and implemented to help students locate relevant books. Also, an additional feature which adds books to the shelf for future reference was included to enhance accessibility and efficiency of the system. The web application was implemented on a live server (Namecheap) which is one of the most effective live servers in Nigeria. Furthermore, the system was evaluated with one hundred and fourteen (114) students, and the results of the evaluation carried out on the system emphasized its usefulness in terms user friendliness (77%), user experience (86%), interface appearance (75%), system loading speed (82%), platform compatibility (78%), recommendation accuracy (80%) and recommendation reliability (84%). Therefore, the system could be used to solve students’ problems with regards to the challenges faced with the use of physical and conventional e-libraries.